A unique mitochondrial gene bock inversion in Antarctic Trematomin fishes: A cautionary tale ... - Patel, S.; Evans, C. W.; Stuckey, A.; Matzke, N. J.; Millar, C. D. (Dryad, 2022)
Many Antarctic notothenioid fishes have major rearrangements in their mitochondrial (mt) genomes. Here we report the complete mt genomes of three trematomin notothenioids: the bald notothen (Trematomus (Pagothenia) borchgrevinki); the spotted notothen (T. nicolai); and the emerald notothen (T. bernacchii). The three mt genomes were sequenced using next-generation Illumina technology, and the assemblies verified by Sanger sequencing. When compared with the canonical mt gene order of the Antarctic silverfish (Pleuragramma antarctica), we found a large gene inversion in the three trematomin mt genomes that included tRNAIle, ND1, tRNALeu2, 16S, tRNAVal, 12S, tRNAPhe and the control region. The trematomin mt genomes contained three intergenic spacers, which are thought to be the remnants of previous gene and control region duplications. All control regions included the characteristic conserved regulatory sequence motifs. Although next-generation DNA sequencing technology has allowed the rapid and cost-effective ... : See manuscript for details. ...